Strengthening Organizational and Digital Marketing in Sedau Tourism Village - Dodi Wirawan Irawanto; Dian Ari Nugroho; Yosabah Zahro (Poltanesa, 2025)
This community service program aimed to strengthen the institutional capacity of the Tourism Awareness Group and enhance product competitiveness among coffee micro, small, and medium enterprises (MSMEs) in Sedau Tourism Village, West Lombok. Recognizing the interconnected challenges of weak organizational structure and unbranded, low-visibility products, the program implemented a participatory action research (PAR) based intervention that integrated organizational development with hands-on technical mentoring. Over two intensive days in June 2025, 8 Tourism Awareness Group members and 9 coffee MSME owners co-created tangible outputs through facilitated workshops and practical sessions. These included a collectively agreed vision-mission document, end-to-end coffee production standard operating procedures (SOPs), and culturally grounded packaging designs incorporating Sasak heritage motifs. A unified brand identity emerged from collaborative discussions, crystallized in the slogan “Kopi Sedau Jadi Tau” (“Once You Try Sedau Coffee, You’ll Know”). During digital marketing training, participants actively created or updated WhatsApp Business and Instagram profiles. Importantly, the packaging designs were printed and immediately adopted for commercial use, demonstrating early-stage implementation. Consistent with PAR principles, success is defined not by individual competency gains due to the absence of pre-post assessments but by the co-creation, local ownership, and immediate application of contextually relevant solutions. This integrated model offers a replicable framework for tourism village development that balances institutional strengthening with product-level innovation, laying a practical foundation for future competitiveness in regional and national markets.